Probiotic Supplementation in Aged Human Subjects Counteracts Leukocyte Telomere Attrition Rate. - Coman, Maria Magdalena; Torbidoni-Baldassari, Benedetta; Occhigrossi, Lucia; Deiana, Giovanni; Silvi, Stefania; Verdenelli, Maria Cristina; Napolioni, Valerio (Journal of Medicinal Food, 2026)
Probiotic supplementation is gaining attention for its role in maintaining health and enhancing the quality of life of the elderly. Leukocyte telomere length (LTL) is a biomarker of cellular aging, with shorter LTL associated with cardiovascular morbidity and mortality. This study explored whether probiotics could counteract LTL attrition in an ethnically homogeneous cohort of older adults over a 6-month period. Samples were selected from the PROBIOSENIOR trial, a randomized, double-blind, placebo-controlled study involving 46 participants (≥60 years). Participants were randomized to receive either SYNBIO® probiotics (5 × 109 CFU/daily dose) or a placebo for 6 months. Genomic DNA was extracted from blood samples at baseline, and 6 months later, LTL measures were obtained via quantitative PCR. A general linear model assessed the "treatment x time" interaction as the main outcome. LTL was successfully assessed for all participants (N = 46 × 2 time points). Statistical analysis revealed a significant "treatment x time" interaction (P =.034), indicating a reduced LTL attrition rate in the probiotic group compared with the placebo group. A 6-month supplementation with SYNBIO probiotics significantly reduced LTL attrition in an ethnically homogeneous cohort of elderly adults. These findings suggest that probiotics may serve as a simple and effective intervention to mitigate cellular aging and promote healthy aging.